The Four-Sided Triangle of Ethics in Bioprospecting: Pharmaceutical Business, International Politics, Socio-Environmental Responsibility and the Importance of Local Stakeholders - Rose, Janna; Quave, Cassandra L; Islam, Gazi (Ethnobiology and Conservation, 2012)
Bioprospecting, a vital step in the pharmaceutical production process, is also one of the most controversial and socially complex aspects in the pharmaceutical industry. The current conceptual paper reviews and theorizes this controversial sector by laying out the key elements of social, political and economic conflict involved in bioprospecting, from the point of view of the diverse stakeholders involved in the activity. First, we discuss the bioprospecting phenomenon as a high-risk, initial-stage research and development (R&D) activity that involves ethical, legal and economic uncertainties. After describing these uncertainties, we show how they are exacerbated by the unique cognitive frames that the main actors in this area – private companies, government actors, social and environmental activists, and local communities – use in framing the motives, norms, and rights surrounding bioprospecting. Juxtaposing actors in this way allows an opening for potential dialogue among the different stakeholders, and we follow our exposition by sketching a model for increased cooperation. Our model highlights the unique contributions of each actor, suggesting that a socially responsible form of natural resource use can promote both local and global benefits. Lastly, we discuss how bioprospecting can be utilized as a key tool in ethnobiological conservation efforts by aiding local stakeholders in the creation of economic value for their traditional knowledge and environmental assets.